Subspace Based Identification of Broadband Electrical Models from Frequency Response Data - Stelzer, Andreas; Neumayer, Roland; Weigel, Robert (AEÜ - International Journal of Electronics and Communications, 2003)
The generation of broadband equivalent circuit models for time-domain analysis of complex structures or components characterized by frequency-dependent network parameters is of great interest in microwave theory. In this paper, a recently developed frequency-domain subspace identification algorithm is applied to generate multi-port circuit models for passive microwave devices characterized by admittance, impedance, or scattering parameter data. The proposed method combines non-parametric minimal order realization and efficient passivity check. It is suitable for simulating linear sub-networks characterized by frequency response data in a general circuit environment consisting of lumped/distributed elements and nonlinear devices. The synthesized networks are compatible with SPICE-based circuit simulators, as is demonstrated by numerical examples.
elib2cris::1512001600,stelzer2003